2014
DOI: 10.1017/s002221511400156x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and audiological effects of mechanical trauma associated with the placement of an intracochlear electrode, and the benefit of corticosteroid infusion: prospective animal study

Abstract: The findings suggest that continuous dexamethasone infusion is beneficial for preventing the loss of hair cells and neurons associated with early and late periods of intracochlear electrode trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…ABR thresholds, DPOAE amplitude, and DPOAE thresholds consistently indicated hearing loss in all frequencies immediately after the electrode insertion in the present study. This acute hearing impairment is consistent with the findings of previous studies Lee et al, 2013;Burghard et al, 2014;Malkoc et al, 2014).…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…ABR thresholds, DPOAE amplitude, and DPOAE thresholds consistently indicated hearing loss in all frequencies immediately after the electrode insertion in the present study. This acute hearing impairment is consistent with the findings of previous studies Lee et al, 2013;Burghard et al, 2014;Malkoc et al, 2014).…”
Section: Methodssupporting
confidence: 93%
“…Sustained perfusion of dexamethasone via an osmotic pump into the cochlea for 8 days after cochlear implantation demonstrated a considerable recovery of ABR thresholds in guinea pigs (Eshraghi et al, 2007). Continuous infusion for 14 days after cochlear implantation suggested a benefit for the prevention of hair cell loss (Malkoc et al, 2014). Astolfi et al (2014) summarized three main phases of damage caused by cochlear implantation: (1) insertion trauma within the first 2 days, (2) inflammation within 2 weeks, and (3) an intracochlear chronic fibrosis reaction.…”
Section: Methodsmentioning
confidence: 95%
“…Many experimental studies in animals have demonstrated that the use of corticosteroids is able to preserve hearing thresholds, increase the survival of hair cells and spiral ganglia, and decrease the formation of new fibrotic tissue within implanted cochlea (20)(21)(22)(23)(24)(25)(26)(27). Clinical studies demonstrate lower impedances and improved preservation of low-frequency residual hearing in patients when corticosteroids are used in CI surgery (28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic glucocorticoids were first synthesized in 1957 and approved for medical use in 1961. Animal testing has shown that the use of glucocorticoids dampens foreign body reactions; consequently, the survival of hair cells and spiral ganglions is increased and fibrosis reduced (Eshraghi et al, 2007 ; Kuthubutheen et al, 2015 ; Malkoc et al, 2014 ). The first clinical pilot studies indicated that the use of glucocorticoids in cochlear implant surgery could prevent increased electrical impedance, improving preservation of the dynamic range (Bas et al, 2016 ; Kuthubutheen et al, 2017 ; Prenzler et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%